Analysis of productivity levels and economic efficiency in agriculture - Suryanarayana Raju, S. K. V. (India : Chug, 1987)
Study conducted in Vishakhapatnam District, Andhra Pradesh.
Includes index and bibliographical references
Keywords: Agricultural productivity -- India -- Vishākhapatnam District